Differential effects on tumor progression by APOBEC3A, APOBEC3B, and APOBEC3H Haplotype I in a breast cancer mouse xenograft model - Granadillo Rodríguez, Milaid; Wong, Lai; Shayeganmehr, Arzhang; Pellegrina, Diogo; Vizeacoumar, Frederick S.; Vizeacoumar, Franco J.; Helmy, Mohamed; Chelico, Linda (Frontiers in Genetics, 2026)
IntroductionThe APOBEC3 family of cytidine deaminases induces somatic mutations that are highly prevalent in cancers, but the functional consequences remain largely unknown.MethodsTo determine these consequences, we exposed MCF7 tumorigenic breast epithelial cells to APOBEC3A, APOBEC3B or APOBEC3H Haplotype I.ResultsComparative analysis between cells pre and post ‐APOBEC3 exposure revealed fewer deamination‐dependent γH2AX foci post‐APOBEC3 exposure, despite maintaining APOBEC3 protein expression. In a mouse xenograft model, high expressing, but not low expressing APOBEC3A‐exposed cells caused increased tumor progression. In contrast, high expressing, but not low expressing APOBEC3B‐exposed cells decreased tumor size. APOBEC3H Haplotype I‐exposed cells stochastically increased tumor progression independent of expression levels. Consistent with tumor data, RNA‐seq showed upregulation of tumor enhancing pathways only in cells that enhanced tumor progression.DiscussionThe results indicate that in a breast cancer xenograft model, APOBEC3A and APOBEC3H Haplotype I are more likely to contribute to enhanced tumor progression than APOBEC3B.